First confirmed record of the spearfish remora Remora brachyptera (Lowe, 1839) in the Mediterranean Sea - PAVIČIĆ, MISO; DRAGIČEVIĆ, BRANKO; UGARKOVIĆ, PERO; ŽUŽUL, IVA (Mediterranean Marine Science, 2024)
One specimen of spearfish remora Remora brachyptera (Lowe, 1839) was caught in a bottom trawl in the eastern Adriatic Sea (Croatia) in June 2021. Morphological analysis and genetic barcoding were used for species identification. Despite references to the species inhabiting the Mediterranean Sea, no documented records have been available to substantiate its presence in the basin. This finding represents the first documented record of this species from the Adriatic and Mediterranean Seas.